A bibliometric assessment of progress in marine spatial planning. (May 2021) - Chalastani, Vasiliki I.; Tsoukala, Vasiliki K.; Coccossis, Harry; Duarte, Carlos M.
Abstract: Marine/maritime spatial planning (MSP) is a process to optimise marine space allocation to various activities and the environment by avoiding negative interactions, improving synergies, thereby helping the advance towards a sustainable ocean economy. A bibliometric progress assessment of MSP was performed for the period 2003–2019 to analyse 1323 papers published in the ISI Web of Science and Scopus databases. The analysis revealed that MSP is a relatively new, however rapidly growing research field, as the number of MSP publications increased exponentially, at about 44% per year, between 2003 and 2019. The dominance of the journal "Marine Policy" on MSP publications and the presence of leading authors with government-related positions (i.e. 11%, n = 981) indicate the linkage of MSP to policy and governance. Almost 70% of the MSP publications are case-based indicating MSP's practical orientation. More than half of the authors leading MSP publications are affiliated in Europe, while the majority of reported MSP case studies are undertaken within the European Union. Most, 63%, of all MSP studies (n = 1323) approach the matter in a qualitative manner, whereas only 22% of the quantitative and/or modelling studies (n = 489) are describing MSP applications, suggesting that the development of MSP quantitative and/or modelling methodologies is still at its infancy. The dominance of ecologists among the leading authors of MSP publications outlines the ecosystem-based approach used to address MSP. This bibliometric study draws the landscape of the current state and trends of MSP, outlines gaps and indicates the roadmap for further developments to assist MSP processes. Highlights: Marine spatial planning (MSP) publications increased exponentially, at about 44% per year, between 2003 and 2019. More than 50% of the studies used qualitative methods to conduct MSP. European Union mandated MSP in 2014 and is currently the global leader in its applications. Most MSP studies are led by ecologists, outlining their ecosystem-based nature. MSP is applied in practice with almost 70% of the relevant studies being case-based.